Succinate dehydrogenase deficient gastrointestinal stromal tumor in a three month old boy with a fatal clinical course: a case report and review of literature - Bei-Bei Lv; Jia-Mei Li; Zhi-Gang Yao; Xian-Kui Cheng; Fu-Xin Ren; Wen-Jing Su; Ye-Jun Qin; Zhou Wang; Zhi-xin Cao (BMC, 2021)
Abstract Background Succinate dehydrogenase deficient gastrointestinal stromal tumors (SDH-deficient GISTs), which lack KIT or PDGFRA mutations demonstrate unique clinical and pathological features, and they respond poorly to standard targeted therapy. We herein present a novel case of SDH-deficient GIST in a three-month-old infant's colon mesentery, and he is the youngest patientto date. Case presentation The infantpresented with complaints of blood in the stool. CT showed a 6.3 × 4.6 cm mass in the left lower retroperitoneal. Complete resection of tumor and segmental bowel resection was performed without regional lymphadenectomy. Histologically, tumor cells were distinctive in their multinodular colon wall involvement with interspersed tracts of colon wall smooth muscle. The tumor was composed mainly of epithelioid cells. Immunohistochemically, the tumor cells were positive for Vim, CD117, PDGFR, while negative for SDHB. Mutational analysis showed a synonymous mutation for SDHB and wild-type for KIT and PDGFRA. Two months after surgery, metastases were found and Imatinib was administered. Unfortunately, the disease continued to progress, and the infant died 5 months after surgery. Conclusions SDH-deficient GISTs comprise a subgroup of a relatively rare tumor type and show a number of clinically and biologically unique features, especially for infants. It is of great importance to developing new therapeutic targets and novel specific drugs.